Need Analysis on the Development of Polytechnic English Textbook - Sari Mubaroh; Linda Fujiyanti (Linguistic, English Education and Art (LEEA) Journal, 2022)
This study aims to identify and analyze students' needs for English textbooks that suit their needs. This research method uses a descriptive quantitative method. The results of this study indicate that: (a) all students agree that English is important for them to learn; (b) the existing English textbooks are less attractive for students to learn English; (c) the instructions in the book are not clear and difficult to understand; (d) students need TOEFL material to be studied in class; (e) there are not enough textbooks on campus for students to master the TOEFL; (f) exploration activities are required for students to master the four English skills (listening, speaking, reading, and writing); (g) students need a TOEFL equivalent textbook in the mastery of English both spoken and written. In conclusion, students of the TRPL Polman Negeri Babel Study Program need textbooks that suit their needs. The need for English textbooks with TOEFL equivalence comes from the achievement of study objectives (CPL), TRPL, graduation requirements, and the world of work. Keywords: Needs Analysis, English Textbook, TOEFL